YouTube as an information source for pulmonary rehabilitation in patients with COVID-19: A Cross-Sectional Study - Yıldız Gonca Doğru; Çağlar Karabaş (Genel Tıp Dergisi)
Introduction: Impaired lung function and decreased exercise capacity may have seen in COVID-19. Therefore, the importance of pulmonary rehabilitation stands out. YouTube has been used often for information about health. The aim of the study is to evaluate the content and the quality of YouTube videos of pulmonary rehabilitation in COVID-19. Method: In this cross-sectional study, the keywords were determined and searched in YouTube by two researchers. A total of 282 videos were watched. Video sources, contents, duration, view number, likes, dislikes, and comments were recorded. For assessment of quality, the Global Quality Scale (GQS) and for reliability the Modified DISCERN reliability tool was used. Results: After application of inclusion and exclusion criteria, a total of 135 videos were analyzed. According to the GQS, 27 (20%) of videos were low, 47 (34.8%) of medium, and 61 (45.2%) of high-quality. Non-physician Health personnel shared the most videos (31.1%). The high-quality video source was Non-physician health personnel, Physician, Academic/university, and Health-related website. There was a statistically significant difference in DISCERN score between quality groups and the highest score was in the high-quality group (p